2006
DOI: 10.1017/s1049023x00003277
|View full text |Cite
|
Sign up to set email alerts
|

Precision of In-Hospital Triage in Mass-Casualty Incidents after Terror Attacks

Abstract: Introduction:Proper management of mass-casualty incidents (MCIs) relies on triage as a critical component of the disaster plan.Objective:The objective of this study was to assess the precision of triage in mass-casualty incidents.Methods:The precision of decisions made by two experienced triage officers was examined in two large MCIs. These decisions were compared to the real severity of injury as defined by the Israeli Defence Forces (IDF) classification of severity of injuries and the Injury Severity Score (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 7 publications
0
23
0
5
Order By: Relevance
“…Clinical acumen alone has been shown to be insensitive at predicting serious injury—potentially as low as 47% 22. The TSO (widely used in the UK for second-line triage at casualty clearing stations and hospitals) only has a sensitivity of 59% for those patients needing LSI in this military population.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical acumen alone has been shown to be insensitive at predicting serious injury—potentially as low as 47% 22. The TSO (widely used in the UK for second-line triage at casualty clearing stations and hospitals) only has a sensitivity of 59% for those patients needing LSI in this military population.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the system used, healthcare professionals’ performance in triage is poor,5 even when it is carried out by experienced doctors 6. Undertriage, which consists in missing important patients’ injuries, leads to the inefficient use of available human and material resources.…”
Section: Triage Principles and Instrumentsmentioning
confidence: 99%
“…Performing triage during an MCI ideally requires to assess in a very short time the number of critically injured patients and the availability of treatment resources 1 22. Students’ high performance must be relativised because they were not asked to make triage considering human and material resources and no maximum execution time was allotted.…”
Section: Limitationsmentioning
confidence: 99%
“…The US SALT triage system attempts to address this by describing injuries as minor or unlikely to be survivable, given the available resources 16. While anatomical triage has been out of favour because of its poor reproducibility, low sensitivity in isolation, and impracticality (it involves the need to undress),11 this may be a very sensible course—Israeli experience after bombings showed that while rapid senior clinician assessment alone had sensitivity of only 60%, it had a specificity of over 80% 17. It may be that combining optimised physiological parameters with a senior clinician making an early on-scene assessment, and downgrading where appropriate, may improve the sensitivity without vastly diluting the specificity.…”
Section: Anatomy and Senioritymentioning
confidence: 99%